Hepatoprotective effect of kaempferol glycosides isolated from Cedrela odorata L. leaves in albino mice: involvement of Raf/MAPK pathway - Gihan Farag Asaad; Heba Mohammed Ibrahim Abdallah; Hala Shaaban Mohammed; Yousra Ahmed Nomier (Wolters Kluwer Medknow Publications, 2021)
Background and purpose: Paracetamol is the most implicated xenobiotic in inducing hepatotoxicity. Our study aimed to determine the impact of some kaempferol glycosides isolated from the leaves of Cedrela odorata L. on paracetamol hepatotoxicity. Experimental approach: The methanolic extract of dried leaves of C. odorata L. was subjected to the combination of spectroscopic methods (1H and 13CNMR). Six kaempferol glycosides were isolated: kaempferol-3-O-β-D-glycopyranoside (astragalin), kaempferol-3-O-β-L-rhamnopyranoside, kaempferol-3-O-β-D-rutinoside, kaempferide-3-O-β-D-rutinoside, kaempferide-3-O-β-Drutinosyl-7-O-β-D-rhamnopyranoside, and kaempferol-3-O-β-D- rutinosyl-7-O-a-D-arabinopyranoside. Fifty-four female Swiss Albino mice were divided randomly into 9 groups including[1] control negative (1 mL/kg saline; IP),[2] control positive (paracetamol 300 mg/kg; IP),[3] silymarin 50 mg/kg (IP). Animals of groups 4-9 were injected with 6 different samples of isolated compounds at 100 mg/kg (IP). One h later, groups 3-9 were injected with paracetamol (300 mg/kg IP). Two h later, tissue samples were taken from all animals to assess nitrotyrosine, c-Jun N-terminal protein kinase (c-JNK), Raf -1kinase, and oxidative stress biomarkers viz. reduced glutathione (GSH) and malondialdehyde (MDA). Findings/Results: Isolated glycosides had a prominent anti-apoptotic effect via inhibition of c-JNK and Raf-1 kinase. They also exerted a powerful antioxidant effect by modulating the oxidative stress induced by paracetamol via increasing GSH, reducing MDA and nitrotyrosine concentrations compared to positive control. The glycoside[1] showed a better effect than silymarin (standard) in ameliorating the formation of nitrotyrosine, Raf-1 kinase, c-JNK, and GSH. Conclusion and implication: Kaempferol glycosides isolated for the first time from C. odorata L. leaves exerted antioxidant and antiapoptotic effects via amelioration of oxidative stress and inhibition of Raf/ MAPK pathway.